HUBUNGAN KEPATUHAN PENERAPAN KOMUNIKASI SBAR DENGAN KESELAMATAN PASIEN PADA PERAWAT DI RSU KABUPATEN TANGERANG - Dewi, Vidya Cynthia; Sriningsih, Nining; Winarni, Lastri Mei (BIMIKI (Berkala Ilmiah Mahasiswa Ilmu Keperawatan Indonesia), 2021)
Background:Patient safety is a system designed to improve the overall safety of patient care. One of the goals of patient safety is to improve effective communication, to improve communication effectively, SBAR communication techniques are needed. Objective: To determine the relationship between compliance with the application of SBAR communication with patient safety. Method: analytic descriptive with cross sectional approach. Respondents were taken using the Accidental Sampling technique, a sample of 108 nurses from the NICU, ICU, IGD and HCU nurses. Results: Chi-square test results obtained p-value = 0.076> 0.05 which means there is no significant relationship between compliance with the application of SBAR communication with patient safety. Conclusions and recommendations: The results showed no relationship between compliance with the application of SBAR communication with patient safety. It is expected that health services can implement a formal system and training on effective communication.